Overcoming Temperature‐Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core‐Shell Approach. (5th February 2022) - Kalancha, Violetta; These, Albert; Vogl, Lilian; Levchuk, Ievgen; Zhou, Xin; Barr, Maïssa; Bruns, Mark; Bachmann, Julien; Virtanen, Sannakaisa; Spiecker, Erdmann; Osvet, Andres; Brabec, Christoph J.; et al.
Abstract: Transparent electrodes consisting of silver nanowires (Ag NWs) are a solution‐processed alternative to commonly used indium tin oxide electrodes. Here, Ag NW electrodes protected by a tin oxide (SnOx ) are explored and unprecedented thermal stability is found. While unprotected Ag NW electrodes fail at 250 °C, the SnOx Ag NW electrodes remain stable for 40 h at 250 °C and withstand high temperatures up to 500 °C for short times. First, an optimized method of synthesis that provides uniform Ag NWs with high reproducibility is used. Afterward, a SnOx shell is formed in a wet chemical reaction. Fabrication of highly conductive electrodes requires thermal annealing at 300 °C for 5 min under ambient atmosphere. Electrodes with a sheet resistance as low as 20 Ω sq ‐1 and visible transmittance of 84% are demonstrated. It is shown that a ≈2 nm thick SnOx shell effectively protects the Ag NWs in a temperature range between 200 and 500 °C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 °C. It is strongly anticipated that these improvements in the stability of Ag NWs open a large field of further investigations and applications. Abstract : Silver nanowire electrodes protected by a tin oxide shell exhibit unprecedented thermal stability. The ≈2 nm SnOx shell effectively protects the silver nanowires (Ag NWs) at temperature ranges from 200 to 500 °C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 °C.